Social studies for primary schools - Bakare, Adisa; Belgore, Ayisha; Harrison, Eniola (Farafina Educational, 2008)
Umschlag: "Primary 4: This book introduces children to the concepts of citizenship, leadership and government in Nigeria and more broadly."